“Mejoramiento tecnológico de la cecina y evaluación de empaques flexibles durante el almacenamiento - Águila Hidalgo, Werlin Del (2000)
The present investigation work "Technological Improvement of the Cecina and flexible Packings Evaluation during the storage", was developed in the Laboratories of Analysis and composition of the foods, quality control, and Microbiology and Fermentation of the Agroindustrial Engineering Faculty of the National University of San Martín. The investigation was carried in two stages 1) Study ofthe dried- smoked ofthe cecina and 2) packings evaluation flexibles during the storage of cecina. for the smoked dried study, is praparó filets of pork meat of 12 cm. long, 12 cm. broad and 0.7 cm. of thickness originating from brazuelo and leg, humid salation in a solution of 12° Be during 01 hour to establish the curve of dried and the speed of dried at temperatures of 40, 50 and 60° C and adjusted to a dampness of 35, 40 and 45%. being Obtained as parameter the best from dried to , 50º C by 4 hours and 12 minutes (balance dampness X*= 0:225 gr. H20 /gr. m.s., critical dampness Xc = 0.48 gr. lliO/gr. m.s. and a constant speed of dried Re= 0.000066 gr./cm2x min.) and a final dampness of 40% in wet base; the one which was confirmed as treatment the best through the evaluation sensorial and analysis proximal. the cecina obtained possesses 39.78% of protein, fat 13.8%, ash 48% and humidity 40%. During the storage at temperature of 37ºC and 28±2ºC ( ambient temperature) in flexible packing (Cellophane, politileno of high density, aluminium and bilaminado ), were evaluated the chemistry properties ( iodine i:odex, peroxido and acidity) in the cecina .. The variation of these properties was greater to 37ºC in polyethylene, cellophane and aluminium, finding a value of 0.09% and 0.082% and 0.025% of acid oleico ( acidity index), index of peroxido (Milieq/Kg of fat) 34, 28, 20; iodine index (%) 88, 81, 100 respectively to 90 storage days and for packing bilaminado is maintained constant. estadísticamente there is meaningful difference between the four studied packings, being the bilaminado, the one which proteje better the characteristics of the cecina. test that it is confirmed by the judges of the Evaluation Sensorial, who qualify that to. the product as good in the periodo of 90 days and the kindness microbiological ofthe cecina (absence as fungi).